A Vinylic Rotaxane Cross‐Linker Containing Crown Ether for Hydrophilic and Hard Rotaxane‐Networked Polymers. Issue 1 (7th June 2019) - Sawada, Jun; Aoki, Daisuke; Sogawa, Hiromitsu; Nakajima, Ken; Takata, Toshikazu
Abstract : Rotaxane‐cross‐linked polymers (RCP), which have rotaxane structures at the cross‐link points, show unique physical properties originating from the movable cross‐link points. Herein, poly(N, N‐dimethylacrylamide) (PDMAAm) and poly(N‐isopropylacrylamide) (PNIPAm) which are well known as hydrophilic polymers and whose glass transition temperatures are much higher than room temperature, were applied as matrix polymers for RCPs. These RCPs are easily and successfully synthesized by radical polymerization of vinyl monomers in the presence of small amounts of [2]rotaxane cross‐linker (RC) comprising one wheel and one axle component with a methacrylate group on each component. As the result, PDMAAm‐based RCP without any solvents and PNIPAm‐based RCP swelled with water were much tougher than corresponding covalently cross‐linked polymers. It is confirmed that RC endows both of the hard polymer networks and soft hydrogels with toughness.